2008
DOI: 10.1016/j.jcf.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Scedosporium apiospermum spondylitis in a cystic fibrosis patient

Abstract: We report the first case of multifocal Scedosporium apiospermum spondylitis in a cystic fibrosis patient. The infection, which occurred during voriconazole prophylaxis, disseminated contiguously from the base of the left lung and pleura and spread to vertebrae via the epidural space. S. apiospermum osteoarticular infections are rare, and are difficult to diagnose and cure because of their resistance to anti-fungal drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…The moderately high MIC for caspofungin found in this study has also been reported by others (8). Despite these high in vitro MICs, both caspofungin and terbinafine have been associated with a favorable outcome in clinical practice, highlighting that the results of antifungal susceptibility testing must be considered with caution since no correlation between MIC data and clinical success has been described to date for Scedosporium/ Pseudallescheria (16,17,22). Recent advances in molecular methods have led to a revision of Scedosporium/Pseudallescheria taxonomy, revealing that Pseudallescheria boydii is a species complex.…”
Section: Vol 48 2010supporting
confidence: 80%
See 1 more Smart Citation
“…The moderately high MIC for caspofungin found in this study has also been reported by others (8). Despite these high in vitro MICs, both caspofungin and terbinafine have been associated with a favorable outcome in clinical practice, highlighting that the results of antifungal susceptibility testing must be considered with caution since no correlation between MIC data and clinical success has been described to date for Scedosporium/ Pseudallescheria (16,17,22). Recent advances in molecular methods have led to a revision of Scedosporium/Pseudallescheria taxonomy, revealing that Pseudallescheria boydii is a species complex.…”
Section: Vol 48 2010supporting
confidence: 80%
“…According to both in vitro and in vivo studies, voriconazole could be the most effective antifungal agent, but no recommendations regarding the optimal antifungal therapy for scedosporiosis have yet emerged (12,29). In particular, the benefit of antifungal combination therapy has not been clearly established, despite the increasing number of reports describing a favorable outcome obtained with voriconazole in combination with terbinafine and/or caspofungin (15)(16)(17)22). The in vitro study of 35 antifungal combinations against S. apiospermum and S. prolificans describing a potent synergy between azole drugs and echinocandins will probably reopen the debate on combination therapy (8,23).…”
Section: Vol 48 2010mentioning
confidence: 99%
“…Diabetes is a common complication of CF, and lung transplantation remains the ultimate treatment of CF patients; both situations are associated with a defective immune response and a risk for a disseminated fungal infection. Considering the low susceptibility of S. apiospermum and the tendency of this fungus to disseminate in immunocompromised patients (24,44), it may be important to detect airway colonization by this fungus as early as possible and to initiate rapidly an appropriate antifungal therapy in order to eradicate it before chronic colonization can develop.…”
Section: Vol 47 2009 Molecular Detection Of Fungi In Cf Patients 149mentioning
confidence: 99%
“…Scedosporium species are the second most frequently recovered fungi, after Aspergillus fumigatus (4). Although invasive scedosporiosis is reportedly rare in CF prior to lung transplantation (11), colonization may be a risk factor for invasive disease posttransplantation, with associated high mortality (14,19,(21)(22)(23). The impact of airway colonization by Scedosporium spp.…”
mentioning
confidence: 99%